(untitled) (Swiss Medical Weekly, 2023)
BACKGROUND: Given their high-risk resident population, nursing homes were critical institutions in the COVID-19 pandemic, calling for continued monitoring and vaccine administration to healthcare workers and residents. Here, we studied long-term severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) immunity in vaccinated and unvaccinated healthcare workers and residents of a nursing home in Switzerland between February 2021 and June 2022. METHODS: Our study comprised 45 participants, of which 39 were healthcare workers and six were residents. All participants were offered a maximum of three mRNA vaccine doses (Pfizer/BioNTech, BNT162b2) in December 2020, January 2021, and November/December 2021. Thirty-five participants received three vaccinations, seven either one or two, and three remained unvaccinated. We collected four blood samples: one in March 2021 and three during follow-ups in November 2021, February 2022, and June 2022. We performed a multifactorial serological SARS-CoV-2 assay (ABCORA) for immunoglobulin G, A, and M responses to spike (receptor-binding domain, S1, and S2) and nucleocapsid (N) proteins. Furthermore, we assessed predicted neutralisation activity based on signal over cutoff in ABCORA. We collected epidemiological data from participants via a standardised questionnaire. RESULTS: Thirty-two (71%) of the 45 participants showed hybrid immunity from combined vaccination and previous infection; 10 (22%) had only vaccine-induced immunity; and three (7%) had only post-infection immunity. Participants with hybrid immunity showed the highest predicted neutralisation activity at the end of the study period (median Sum S1 = 273), and unvaccinated participants showed the lowest (median Sum S1 = 41). Amongst participants who reported a SARS-CoV-2 infection, median Sum S1 levels increased with the number of vaccinations (p = 0.077). The healthcare worker group showed a significant time-dependent decrease in median Sum S1 after base immunisation (93% decrease, p = 0.0005) and the booster dose (26% decrease, p = 0.010). Predicted neutralisation activity was lower amongst residents (adjusted ratio of means [AM] = 0.7, 95% confidence interval [CI] = 0.3–1.0) and amongst smokers (AM = 0.5, 95% CI 0.3–0.8). Activity increased with the number of vaccinations (booster: AM = 3.6, 95% CI 1.5–8.8; no booster: AM = 2.3, 95% CI 0.9–2.5). Positive SARS-CoV-2 infection status tended to confer higher predicted neutralisation levels (AM = 1.5, 95% CI 0.9–2.5). CONCLUSIONS: Our study of the long-term serological course of SARS-CoV-2 in a nursing home showed that the first SARS-CoV-2 booster vaccine was essential for maintaining antiviral antibody levels. Hybrid immunity sustained SARS-CoV-2 immunity at the highest level. In critical settings such as nursing homes, monitoring the SARS-CoV-2 immune status may guide booster vaccinations.